2011
DOI: 10.1161/circulationaha.111.046821
|View full text |Cite
|
Sign up to set email alerts
|

Heparin Elevates Circulating Soluble fms-Like Tyrosine Kinase-1 Immunoreactivity in Pregnant Women Receiving Anticoagulation Therapy

Abstract: Background-Alterations in circulating levels of pro-and antiangiogenic factors have been associated with adverse pregnancy outcomes. Heparin is routinely administered to pregnant women, but without clear knowledge of its impact on these factors. Methods and Results-We conducted a longitudinal study of 42 pregnant women. Twenty-one women received prophylactic heparin anticoagulation, and 21 healthy pregnant women served as controls. Compared with gestational age-matched controls, heparin treatment was associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
40
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 42 publications
3
40
3
Order By: Relevance
“…Of potential concern is a recent finding by Rosenberg et al 34 showing that heparin treatment during pregnancy is associated with increased sFlt-1 levels. This increase was detectable after the 28th week of pregnancy in women who, for various reasons, were treated with prophylactic or therapeutic doses of mostly LMWH but in whom pregnancy course and outcome were uneventful.…”
Section: Factors Influencing the Sflt-1/plgf Ratiomentioning
confidence: 99%
“…Of potential concern is a recent finding by Rosenberg et al 34 showing that heparin treatment during pregnancy is associated with increased sFlt-1 levels. This increase was detectable after the 28th week of pregnancy in women who, for various reasons, were treated with prophylactic or therapeutic doses of mostly LMWH but in whom pregnancy course and outcome were uneventful.…”
Section: Factors Influencing the Sflt-1/plgf Ratiomentioning
confidence: 99%
“…In a recent meta-analysis, Ziakas et al concluded that heparin plus LDA is not more effective than LDA alone in treating women with APS-related fetal deaths but at least one of the trials included in that meta-analysis included a mixed population of patients only some of whom had APS (Ziakas et al 2010). Moreover, a number of studies have shown that heparin promotes the placental release of sFlt1 (Carroll et al 2011, Rosenberg et al 2011, an anti-angiogenic factor associated with pre-eclampsia (Maynard et al 2003). However, in vitro studies indicate that vitamin D may reverse this LMWH-induced trophoblast sFlt1 secretion (Gysler et al 2015).…”
Section: Treatmentsmentioning
confidence: 99%
“…However, LMWH up-regulated soluble fms-like tyrosine kinase receptor-1 (sFlt-1) secretion independently of aPL through shedding of the extracellular domain of Flt-1 receptor. 66 The complicated effects of heparin may explain why women with RPL, who were treated with heparin to prevent early pregnancy loss, have inconsistent outcome and still remain at increased risk of developing later obstetrical complications such as pre-eclampsia. 67 In a recent clinical trial, heparin treatment was reported to be associated with increased circulating levels of sFlt-1 in the third trimester without increased growth restriction, and serum of heparintreated cases inhibited both basal and vascular endothelial growth factor-induced capillary-like tube formation.…”
mentioning
confidence: 99%
“…67 In a recent clinical trial, heparin treatment was reported to be associated with increased circulating levels of sFlt-1 in the third trimester without increased growth restriction, and serum of heparintreated cases inhibited both basal and vascular endothelial growth factor-induced capillary-like tube formation. 66 Therefore, upregulation of circulating sFlt-1 immunoreactivity in pregnancy seems not always to be associated with adverse outcomes and whether heparin has any effect to promote angiogenesis is in question. 66 …”
mentioning
confidence: 99%
See 1 more Smart Citation